Preliminary study of heavy metals pollution in freshwater fishes of Sungai Simpang Empat, Penang. / F. Widad and M. Abdullah - F., Widad; M., Abdullah (Universiti Teknologi MARA, Negeri Sembilan, 2013)
A study was conducted to determine heavy metals content in different body parts of fish collected from five sampling stations in Sungai Simpang Empat, Penang from July to December, 2005. The liver, head, gills, muscles and bones of dried fish samples were extracted by the AOAC acid digestion method whilst iron (Fe), zinc (Zn), manganese (Mn), lead (Pb), chromium (Cr), copper (Cu), nickel (Ni) and cadmium (Cd) were analyzed by atomic absorption spectrophotometry. Based on Interim National Water Quality Standard for Malaysia (INWQS), dissolved oxygen, pH, conductivity, ammonia, sulphate, nitrate and phosphate were within the recommended levels suggested for fish to survive except for turbidity levels in some stations, exceeding the recommended of 50 mg/L limit. Fe was accumulated at the highest levels while Cd was the lowest. Only Fe and Mn levels have exceeded the permissible limit of the Malaysian Food Act (1983) and Food Regulations (1985). In most of the fish, liver accumulated the highest concentration of all heavy metals compared to head, gills, muscles and bones. Snakeskin gouramy or Sepat Siam (Trichogaster pectoralis) and black tilapia (Oreochromis mossambicus) are good candidates for potential bioindicator for metals pollution in this study.